Thermal management of 3D integrated circuits with microchannel-based liquid cooling - Qian, Hanhua (2014)
The emerging three dimensional integrated circuit (3DIC) technology has offered promising solutions to problems faced by today’s 2D large-scale-integration (LSI) such as long propagation delay, high power consumption and limited I/O bandwidth. Unfortunately, the stacking nature of 3DICs exacerbates the existing thermal problems due to the simultaneous increase of power density and thermal resistance. This thesis studies the thermal management problem of 3DIC with microchannel-based liquid cooling. Specifically, a compact thermal model is developed in order to accurately simulate the steady state temperature of 3D systems with both heatsink and microfluidic cooling. A runtime proactive thermal management scheme, which adjusts flow rate according to predicted future cooling demand is proposed based on this thermal model. Thermal balancing through channel clustering, splitting and scaling techniques are also investigated and new algorithms are proposed for their implementation.